On the Viscosity of Ag/Oil Based Nanofluids: A Correlation. Issue 1 (20th September 2015) - Aberoumand, Sadegh; Jafarimoghaddam, Amin; Aberoumand, Hossein; Javaherdeh, Kourosh
Abstract : An oil based nanofluid including silver as to be nanoparticles was created by EEW method as a one‐step method in three different volume fractions have been experimentally studied. Assessing the stability and viscosity of the nanofluids was involved in this work. The results show that the nanofluids behave in both of Newtonian and non‐Newtonian in different volume concentrations. Also, an enhancement in viscosity of nanofluids has been recognized. In addition, based on the experimental results of this study and the other previous published studies on the oil based nanofluids, a correlation for predicting viscosity of oil based nanofluids has been developed and a good agreement between the experimental viscosity of applied nanofluids in this study and the predicted one has been achieved.